Influence of breed and parasite challenge on the immune response to naturally acquired intestinal nematode infection in sheep - Albuquerque, A. C.A. [UNESP]; Almeida, F. A. [UNESP]; Bassetto, C. C. [UNESP]; Lins, J. G.G. [UNESP]; Amarante, A. F.T. [UNESP] (Cambridge University Press (CUP), 2022)
Natural infection by intestinal nematodes was assessed in Santa Ines and Ile de France sheep breeds, over a five-month grazing period, with emphasis on the development of the immune response in lambs under two anthelmintic treatment regimens. Nineteen Santa Ines and 19 Ile de France male lambs were allocated into two treatment groups: animals under suppressive treatment with anthelmintics; and animals under targeted selective treatment (TST). The nematodes Trichostrongylus colubriformis and Strongyloides papillosus showed the highest infection intensity in the TST animals in both breeds. Parasite-specific immunoglobulin G levels were significantly higher and more rapidly induced in Santa Ines lambs. Additionally, these lambs had higher levels of parasite-specific immunoglobulin A in intestinal mucus. Animals under TST had higher means of mast cells and globule leukocytes in the intestinal mucosa due to longer and greater parasite challenge in comparison with the suppressive group. A breed effect (P < 0.05) was recorded for mast cells, with Santa Ines lambs presenting the highest counts. Although Santa Ines lambs had lower intestinal nematode counts than Ile de France lambs, they had shown a large variation in T. colubriformis burden, with most of them presenting a marked worm burden, despite showing an earlier and more intense immune response to intestinal nematode infection.
Keywords: Anthelmintic treatment; IgA; Intestinal nematodes; Mast cells